2018
DOI: 10.1186/s13075-018-1780-z
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacovigilance in juvenile idiopathic arthritis patients treated with biologic or synthetic drugs: combined data of more than 15,000 patients from Pharmachild and national registries

Abstract: BackgroundThe availability of methotrexate and the introduction of multiple biological agents have revolutionized the treatment of juvenile idiopathic arthritis (JIA). Several international and national drug registries have been implemented to accurately monitor the long-term safety/efficacy of these agents. This report aims to present the combined data coming from Pharmachild/PRINTO registry and the national registries from Germany (BiKeR) and Sweden.MethodsDescriptive statistics was used for demographic, cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
67
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 81 publications
(81 citation statements)
references
References 36 publications
7
67
0
Order By: Relevance
“…The background risk for malignancies in JIA patients might be higher than that of the general population. The Pharmachild registry reported a similar rate of malignancies, although with fewer hematopoietic malignancies (13). In a more recent study, they compared patients with JIA who were using TNFi with those who were not using TNFi and found that treatment with TNFi did not appear significantly associated with the development of malignancy (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The background risk for malignancies in JIA patients might be higher than that of the general population. The Pharmachild registry reported a similar rate of malignancies, although with fewer hematopoietic malignancies (13). In a more recent study, they compared patients with JIA who were using TNFi with those who were not using TNFi and found that treatment with TNFi did not appear significantly associated with the development of malignancy (20).…”
Section: Discussionmentioning
confidence: 99%
“…In the Pharmachild registry, demyelination was also a rare event (13). In the Pharmachild registry, demyelination was also a rare event (13).…”
Section: Discussionmentioning
confidence: 99%
“…13 Combined data from juvenile biologic registers suggests that infections are common with single or combined treatment but corticosteroids are the most important factor influencing infection risk. [14][15][16][17][18] Recurrent infection rates are also increased in patients on biologics, with a 14% annual risk of recurrent infection following an index event. 17 Respiratory infections were the most frequent (44% of all events) and increasing age and polypharmacy were significant predictors of infection recurrence.…”
Section: Biologic Agentsmentioning
confidence: 99%
“…Treatments in JIA with synthetic and biologic DMARDs are expected to increase the frequency of common infections and the risk of serious and opportunistic infections (OI) [23,[30][31][32][33][34], including especially tuberculosis in some geographic areas [35][36][37]. In order to tackle the long-term safety and efficacy evaluations, the Paediatric Rheumatology INternational Trials Organization (PRINTO) started in 2011 the "Pharmacovigilance in Juvenile Idiopathic Arthritis patients" (Pharmachild), an observational international registry supported by a European Union grant [38,39].…”
Section: Introductionmentioning
confidence: 99%